Fighting Predatory Journals: A Strategic Solution for the Quality and Sustainability of Scientific Publications in Indonesia - Purnama, Adhy; Riyanto, Setyo; Siswanti, Indra; Nawangsari, Lenny Christina (Social and Economic Bulletin, 2024)
The phenomenon of predatory journals seriously threatens the academic ecosystem, especially in Indonesia, where the pressure to "publish or perish" and low academic literacy exacerbate the situation. Predatory journals offer a fast publication process without adequate peer review, thereby lowering the quality of research, hurting the reputation of academics and institutions, and spreading invalid information. Although many global studies have addressed this issue, there are research gaps related to the Indonesian context, especially strategic solutions that consider regulation, literacy, and management of scientific journals. This research aims to identify the impact of predatory journals, outline the challenges for academics and journal managers, and offer strategic solutions based on Agency and Knowledge-Based Theory. The research method used is descriptive-analytical with a qualitative approach based on secondary data from scientific literature. The results show that the main challenges are low academic literacy, pressure to publish, limited access to reputable journals, and financial exploitation. Strategic solutions include education through programs such as “Think, Check, Submit.” Strengthening regulations, using technology to detect predatory journals, and national and international collaboration. The role of journal managers is vital in maintaining the quality of publications through editorial transparency, certification, technological innovation, and the development of the reviewer community. The implications of this study emphasize the importance of collaboration and academic literacy in creating a healthy academic ecosystem. The novelty research lies in integrating Agency and Knowledge-Based theories in the context of predatory journals in Indonesia, offering relevant and applicable strategic solutions to support the sustainability of high-quality scientific publications.